Development of biofoam from sucrose, furfuryl alcohol, itaconic acid, and ammonium dihydrogen phosphate with enhanced thermal insulation and flame retardancy - Zhu, Wenhao; Dong, Yuhao; Chen, Xinyi; Deng, Shuduan; Lee, Seng Hua; Lum, Wei Chen; Abdullah, Ummi Hani; Zhou, Xiaojian; Zhang, Jun (Elsevier B.V., 2025)
Sucrose was crosslinked with furfuryl alcohol (FA) in the presence of itaconic acid (IA) to synthesize sucrose-furfuryl alcohol-itaconic acid (SFI) resin. Ammonium dihydrogen phosphate (ADP) was subsequently combined with SFI resin to produce SFIA foam. The structure, morphology, mechanical characteristics, thermal properties, and flame retardancy of SFIA foam were evaluated. Spectroscopic analysis verified that sucrose facilitated the crosslinking reaction among FA, IA, and ADP. The SFIA foam possesses a small cell pore size of 278.86 μm and a thick cell wall measuring 65.32 μm. As a result, the SFIA foam possesses exceptional compressive strength of 3.481 MPa, which only marginally decreased to 3.317 MPa after 72 h of UV irradiation. The small cell pore size endows the SFIA foam with exceptional thermal conductivity of 0.054 W·m−1·k−1. Correspondingly, SFIA foam displayed outstanding thermal stability and thermal insulation properties, not to mention exceptional flame retardancy, as evidenced by the high limiting oxygen index (LOI) of 46.1 %. Noteworthily, the SFIA foam has been rated UL-94 V-0. Moreover, the SFIA foam is biodegradable, making it holds significant potential for widespread industrial applications, particularly in sustainable building materials.